Electromagnetic wave detection based on multiband antenna design - Yew, Been Seok; Fwen, Hoon Wee; Lee, Yeng Seng (2016)
Electromagnetic (EM) radiation has been a common concern in most developed and developing countries in terms of the hazard it poses upon human's health and its capabilities of reducing efficiency of electrical and electronic devices in its surrounding. Thus, to overcome this problem, an antenna is playing important role where it should has the function of detecting various hazard of electromagnetic wave. A multi-band microstrip antenna will need to be designed. The antenna design was simulated and the results such as return loss, input impedance, radiation pattern, VSWR, and efficiency were validated and analyzed. Based on the results, it was found that this antenna is able to support modes with resonance of 2.3, 4.5, 4.68 and 5.2 GHz where these resonances are also known as the most high risk EM signal that been exposed by human being in everyday life. The multiband microstrip antenna has been successfully designed by Computer Simulation Technology (CST) microwave studio 2014.